Expression of leptin and its receptor in selected human cancers - preliminary results - Kozak, Agnieszka; Micuła, Andrzej; Wcisło, Gabriel; Anusik, Jacek; Doniec, Jacek; Szenajch, Jolanta; Wiśniewski, Piotr; Z. Pawlak, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2002)
Leptin, a pleiotropic hormone and cytokine, may also play a role in neoplastic transformation. This hypothesis is based on the critical role of leptin signal transducing pathways in the cell proliferation, apoptosis and neoplastic transformation. This article presents the preliminary results of screening of leptin and its receptor mRNA expression in some human cancers: carcinoma cell lines of leukemia (Jurkat, K562) and ovary (OVCAR3, OVP10); ovary non-malignant tumors (3 cases), ovary malignant tumors (4 cases), breast (2 cases), prostate (1 case), kidney (1 case), urinary bladder (3 cases) and testes (1 case) cancers. Total RNA was isolated from cultured cells or from fragments of surgically removed tumors. Then reverse transcripton and polymerase chain reaction were performed. PCR with primers for the house-keeping gene encoding for glyceraldehyde-3-phosphate dehydrogenase was performed to confirm the RNA integrity. PCR with primers for lipoprotein lipase encoding gene was performed to exclude the contamination of tumor fragments by adipose tissue, because lipoprotein lipase encoding gene is expressed in tissue-specific manner in adipose tissue. The primer pair for leptin receptor was designed in the manner which allows to detect the RNA fragment common for four its isoforms. As a positive control for PCR assays RNA from adipose tissue was used in which lipoprotein lipase, leptin and its receptor are expressed. The finding of expression of leptin receptor in Jurkat and K562 cell lines is in accordance with other authors data. The leptin expression was not found neither in OVCAR3 nor OVP10 line, but the leptin receptor expression was found only in OVCAR3 line. In non-malignant ovary tumors neither leptin nor its receptor expression were found. However, the differences of leptin and its receptor expression in malignant tumors of different histological origin and even in cancers of the same origin were found (i.e. in ovary cancer). In some cases of ovary cancer, in renal and testis cancers both leptin and its receptor were expressed, what could suggest the autocrine loop existing. In other cases of ovary cancer, breast and urinary bladder cancers only the leptin receptor was expressed, what could suggest the systemic or paracrine action of leptin.